The Representation of the Relationship Between Center and Periphery in the Contemporary Novel - Amar, Ruth; Saquer-Sabin, Françoise (Cambridge Scholars Publishing, 2018)
This collection of essays offers a comparative perspective on different forms of representation of social hybridity in contemporary novels through various cultural and linguistic lenses. It explores the various subcategories of their interdependent relationships, including power and domination between hegemony and marginality. The book revolves around five axes: namely, writing strategies and reterritorialization; marginality and intermediary spaces; revisited urban spaces; when periphery becomes center; and the modality of confrontation and construction of identity. It focuses on the identific.